Spremljanje izbranih lastnosti tal na ploskvah intenzivnega monitoringa (IM) gozdnih ekosistemov - Marinšek, Aleksander (Gozdarski vestnik, 2024)
Systematic monitoring of forest soils in Slovenia since 1995/96 has enabled the assessment of basic pedological properties and monitoring of changes over time. Since 2003, intensive monitoring at selected sites has also allowed the assessment of cause-effect relationships and the monitoring of soil processes. Analysis of the mineral part of the soil (0-10 cm) shows differences between plots in different locations in Slovenia, but changes in soil parameters during intensive monitoring within individual plots have not changed significantly.A slight increase in organic carbon and total nitrogen has been observed, while the values of the organic carbon/total nitrogen (C/N) ratio and soil pH have remained stable. Despite the differences between the plots, the values of carbon and nitrogen and their ratios are comparable to those of the European 16 km × 16 km grid. Although there are minor changes in the soil properties analysed between the sampling periods (2003-2010 and 2022), the trends are stable. The analysis of forest soil conditions in the intensive monitoring system plots shows minor changes between the first and second sampling periods. Nevertheless, the trends are stable, indicating a logical link between carbon and nitrogen dynamics in forest ecosystems. Further intensive forest soil monitoring activities are crucial to understand soil processes and to identify indicators of future soil health.
Keywords: carbon in soil; dušik v tleh; forest sites; forest soil; forest soil properties; gozdna rastišča; gozdna tla; lastnosti gozdnih tal; monitoring; nitrogen in soil; ogljik v tleh; spremljanje stanja